Scrolling for science: Assessing the quality and accuracy of Crohn’s disease-related content on Instagram reels - Sankirth Madabhushi; Ami Patel; Samantha Tse-Kang; Andrew Liu; Dhruval Amin; Abbas Rupawala (PLoS ONE, 2026)
Background There is a concerning trend of misinformation of healthcare related content on social media. Recent studies have examined themes and narratives about Crohn’s disease but have not quantitatively assessed the accuracy and quality of content on Instagram Reels. Our aim was to assess the quality and accuracy of Instagram Reels about Crohn’s disease and examine differences in content by type of creator, from medical professionals to lay individuals. Methods Seventy-eight top-viewed English-language Instagram Reels tagged with “#crohns” were evaluated. Videos were categorized by creator and content type. Two reviewers evaluated each video for accuracy and quality using an adapted harm/benefit score and the Journal of the American Medical Association (JAMA) benchmark criteria, respectively. Results Seventeen percent of videos were created by medical professionals and 83% by non-medical users. Educational content was significantly more common among medical professionals than other content creators (62% vs 23%; P = 0.005). No significant correlation was found between engagement metrics and either JAMA or harm/benefit scores. Medical professionals had significantly higher JAMA scores than non-medical users (2.5 vs 2, P < 0.001), but there was no significant difference in harm/benefit scores between groups (0 vs 0, P = 0.9601). Videos offering medical advice had the lowest median harm/benefit score (−1), with frequent misinformation noted. Forty-two percent of harmful videos were created by medical professionals. Conclusions The average Instagram Reel about Crohn’s disease was of moderate quality and neutral impact. Accuracy or quality was unrelated to video popularity. While videos by medical professionals had higher JAMA scores, this did not correspond to greater accuracy. Medical advice videos by medical professionals were not more accurate than those by non-medical creators, and multiple harmful videos were created by medical professionals, underscoring the need for critical evaluation of Crohn’s disease-related social media content.